Peningkatan Kompetensi Guru MI untuk Membumikan Media Pembelajaran Digital maupun Non Digital dalam Menciptakan Meaningful Learning - Abdur Rohim; Arezqi Tunggal Asmana; Dhiah Agustina Qahar (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
One of the components that is the standard for educational success is by examining the success of learning. In order to achieve success in learning, there needs to be a method that needs to be done, namely meaningful learning. Meaningful learning should utilize learning media. This is in contrast to the field study conducted at MI Bustanul Ulum. Teachers often apply direct learning models accompanied by explanation and assignment methods. Teachers also never use learning media, either digital-based or like teaching aids that can support the learning atmosphere. This is due to the lack of teacher knowledge and skills in developing learning media. For this reason, with this community service program, we plan to help overcome partner problems. There are 6 stages carried out, namely observation, socialization, workshops and FGDs, design training, media development, evaluation and mentoring. To find out the increase in teacher competence, the normalized gain formula is used which will then be grouped into improvement categories. This community service activity can improve teacher competence. The score for improving teachers' ability to understand digital media is 0.46; The score for improving teachers' ability to understand non-digital media is 0.56 and the score for improving teachers' skills in designing media is 0.40. These three improvements fall into the moderate improvement category.